“E-Bazaar” IIUM - lodi, Mohammahd Tahmid; Mehran, Mujib; Zulkifli, Zahidah (UITM Cawangan Johor, 2021)
In a recent research conducted by Bangladesh Agricultural University, it is found that about RM 3.6 billion worth fruits and vegetables perished in a single session. Another report by Jahangirnagar University stated that upto 40% of harvested products especially fruits and vegetables have perished. This huge loss occurred due to the lack of post harvest facilities and a lack of storage system. The purpose of the e-Bazaar application is to create an online platform for farmers and agri-businessmen to sell their harvest and other food items through this e-commerce system and provide a new business model. On the other hand, the buyers are getting an online system to buy their daily groceries and food items online. For the development of the system, System Development Life Cycle, (SDLC) methodology had been implemented to acquire a clear understanding of the processes throughout the project. Farmers, agri-businessmen and existing online system’s business owners had been interviewed and surveys were carried out to obtain their feedback and needs. For the development phase, the researchers carried out the MERN stack technologies to develop the system. The MERN stack consists of 4 technologies which are MongoDB, Express, React Native, Node.js (MERN). E-Bazaar can create a new platform for the farmers and businessmen to conduct their business. It will create a new scope for the farmers to sell their products in bulk and small quantities to a wider range of customers. Many people might get encouraged in this business since people will not require a physical shop and can start the business with small capital. This will create job opportunities and more business opportunities for people in Bangladesh and can be applied in other countries as well.